High intratumoral CD8+ T‐cell infiltration is associated with improved survival in prostate cancer patients undergoing radical prostatectomy. Issue 1 (21st October 2020) - Yang, Yuanquan; Attwood, Kristopher; Bshara, Wiam; Mohler, James L.; Guru, Khurshid; Xu, Bo; Kalinski, Pawel; Chatta, Gurkamal
Abstract: Background: A high density of CD8 + tumor infiltrating lymphocytes (TILs) is associated with improved survival in multiple cancers, but its prognostic role in prostate cancer remains controversial. The aim of our study was to evaluate the prognostic value of CD8 + TILs in prostate cancer patients undergoing radical prostatectomy (RP). We hypothesized that elevated density of CD8 + TILs in the RP specimen would correlate with improved clinical outcomes. This information may be helpful for future immunotherapy clinical trial design and treatment selection. Methods: Tumor microarrays constructed from 230 patients with localized prostate cancers who underwent RP from 2006 to 2012 at Roswell Park Comprehensive Cancer Center were analyzed retrospectively using immunohistochemistry. CD8 + cell density was evaluated using a computerized scoring system. The cohorts were separated by CD8 + TIL density at the 25th percentile (i.e., low <quartile 1 and high ≥quartile 1). The quartile 1 threshold was chosen through a "minimal p  value approach" based on overall survival with correction of significance to adjust for multiple testing. Clinical outcomes were compared in the high versus low CD8 + TIL density groups. Results: One hundred and forty‐nine (65%) patients had high risk diseases (Gleason >7 or pT3/4). The median follow‐up time was 8.4 years. High CD8 + TIL density was associated with improved 5‐year overall survival (98% vs. 91%, p  = .01) and prostate cancer‐specific survival (99% vs. 95%, p  = .04) compared with patients with low CD8 + TIL density. There was a trend toward higher 5‐year biochemical recurrence‐free survival and metastasis‐free survival in the cohort of patients with high CD8 + TIL density (52% vs. 38% and 86% vs. 73%, respectively), although the difference did not reach statistical significance ( p  = .18 and p  = .05, respectively). In a multivariate analysis high CD8 + TIL density was an independent favorable prognostic factor for overall survival (hazards ratio = 0.38; 95% confidence interval: 0.17–0.87;  p  = .02). In contrast to the prognostic value of CD8 + TIL density, the CD8 + cell density in the matched normal prostate tissue was not associated with any clinical outcomes. Conclusion: Intratumoral CD8 + T‐cell infiltration in the RP specimen is independently associated with improved survival after RP in this high‐risk prostate cancer cohort. Pre‐RP immunomodulation that promotes intratumoral CD8 + cytotoxic T‐cell infiltration may be beneficial for this population.